DETERMINATION OF EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS INTERVENING VARIABLE - SILALAHI, ELVIE MARIA; Sembiring, Hendri Sembirinng (Sosiohumaniora, 2020)
The purpose of this research is to analyze the influence of empowerment, interpersonal communication job involvement, onperformanceemployee’s performance, through work motivations. Sample in this research totaled 101 employee’s. Sampling techniques using census method with saturated sampling technique, so the whole population is used as a sample.Variable this research consisting empowerment, interpesonal communication, job involvement, work motivation, employee’s performance. Data collection methods used were questionnaires. Analysis of the data used is multiple linear regression analysis and path analysis using SPSS 24. The results showed direct influence on employee’s performance indicates empowerment and job involvement are supported, but for interpesonal communication is not supported. The Results of research indirect effect on employee’s performance through work motivation showed empowerment dan job involvement are not supported, but interpersonal communication supported. This research is expected to be beneficial for PT. Leo Hupindo to improve employee performance.